Zero Energy Cooling Technology for Storage of Cavendish Banana Fruits - Rahaman, Adams Abdul; Alhassan, Nasiru; Andrews, Agyemang Dua (Journal of Postharvest Technology, 2015)
Postharvest storage solutions are required to increase sales of horticultural  produce and provide producers with options to address the crisis of low market  prices during the harvest season. However, opportunities to develop and adopt  appropriate strategies by farmers in developing countries are limited. There has  been a concern for the need for alternative sources of energy to the stress with  global energy supplies to industries and domestic uses. This project involved  the construction of Zero Energy Cold Chamber (ZECC) for the cooling and  storage of Fresh Banana fruits. This investigation was undertaken to find out  the effects of using Zero Energy Cold Chamber and House Hold Fridge (HHF)  on weight loss, colour changes and consumer acceptance of fresh Cavendish  Banana fruit. A total of 105 fruits were used for the experiment. The Banana  was divided into three to represent the treated and untreated samples. The  respective weights of the fruits were recorded after air drying, stored and  monitored for an experimental period of eight (8) days. Thirty five fruits in  bunches of five was stored in the ZECC, thirty five fruits were also stored in  HHF and thirty five was left at room temperature as control. Completely  Randomized Design (CRD) was the experimental design used. The analysis of  the data was done using a MiniTab version 16. The single factor analysis of  variance was used at 5% alpha level. The Cavendish Banana fruits stored in the  HHF maintained an average colour of 2.0 throughout the entire experimental  period, and the fruits stored in the ZECC produced an average colour of 5.0  when the experiment was terminated on day 8 compared with the CTS with 7.0  as the final stage of Banana ripeness. Average weight loss percentage was  greater (5.91%) in Bananas, which were stored at ZECC than those, which  were stored at HHF with average weight loss (4.90%) on the 8 day. Panelists  preferred Bananas which were stored in ZECC to Banana stored in HHF.  Significant differences were observed on the decay severity of the fruits stored  in the different structures. Considering the performance of the ZECC on the  parameters assessed, it can safely be stated that the ZECC can be adopted by  small scale operators for handling fresh fruits for a reasonable duration in  cooling and storage.
Keywords: Banana; Evaporative cooling Storage; Postharvest quality Consumer acceptance